Culturally Contextualized E-Book Based on West Papua’s Culture to Support Elementary Students’ Mathematical Connection Skills - Muhiddin; Sitti Fithriani Saleh; Irwan Akib (Universitas Pendidikan Ganesha, 2025)
Integrating local cultural context into mathematics learning can provide meaningful learning experiences for students. West Papua is rich in cultural artifacts and practices that can be inspired into learning. This study aims to develop a culturally contextualized electronic mathematics book (e-book) based on West Papuan culture to support elementary school students' mathematical connection skills. This study is a development research project using the Plomp educational design research stage consisting of three stages: preliminary research, development or prototyping, and assessment. The e-book was developed using the Book Creator application. The data sources in this study were community leaders, lecturers, teachers, and students. The instruments used to collect data in this study were questionnaires, interview guidelines, and validation sheets. The e-book contains five steps of student activities: Let's Read, Let's Learn Together, Let's Practice, Let's Adventure, and Let's Tell Stories. The results of the validation and readability tests indicate that the e-book is valid and can be used in mathematics learning. However, teachers expressed the limitations of the devices and internet access needed to read e-books at school.